Study on dynamic changes in land use and ecosystem service value in the Huaihe River ecological economic belt based on multi-scenario simulations - Li, Changai; Wu, Yong; Qiu, Bing; Li, Yaliang; Ning, Lili; Wang, Hui; Liu, Ling; Ma, Jin (Frontiers in Environmental Science, 2025)
This research investigated the changes of land use as well as ecosystem service value (ESV) of the Huaihe River Ecological Economic Belt (HREEB) which is a critical ecological functional zone in China. This research utilised land-use data to analyse the spatiotemporal dynamics of land-use patterns of the HREEB. The patch-generating land-use simulation model was utilized to simulate land-use patterns under three distinct scenarios for the year 2030. The ESV was quantified using the equivalent factor method. Furthermore, Pearson correlation analysis and the geographic detector model were employed to examine the impacts of factors on the ESV. The results showed that (1) From 2000 to 2020, farmlands predominated as the primary land-use type, followed by artificial surfaces, forests and water bodies. The most notable land-use trend was the conversion of farmlands into artificial surfaces. (2) Between 2000 and 2005, the overall ESV rose, but from 2005 to 2020, it decreased. By 2030, the ESV under the ecological protection scenario would higher than other scenarios (3) Land-use types (espacially water bodies and artifical surfaces), NDVI and soil type were identified as the crucial drivers of ESV variation. Thus, our results can offers considerable theoretical insights for formulating environmental conservation and land-use strategies for the region.